Predictive value of transcranial evoked potentials during mechanical endovascular therapy for acute ischaemic stroke: a feasibility study. Issue 6 (10th June 2015) - Shiban, Ehab; Wunderlich, Silke; Kreiser, Kornelia; Lehmberg, Jens; Hemmer, Bernhard; Prothmann, Sascha; Zimmer, Claus; Meyer, Bernhard; Ringel, Florian
Abstract : Background and purpose: Mechanical endovascular therapy (MET) is a promising adjuvant or stand-alone therapy for acute ischaemic stroke caused by occlusion of a large vessel. Real-time monitoring of recanalisation success with regard to functional outcome is usually not possible because these procedures are mainly performed under general anaesthesia. We present a novel application for evoked potential monitoring for real-time evaluation of reperfusion success with respect to functional outcome during MET for acute ischaemic stroke. Methods: Prospective observational study from March 2012 to April 2013 of patients presenting with acute ischaemic stroke who were eligible for MET. Transcranial motor evoked potentials (MEPs) and somatosensory evoked potentials (SSEPs) were measured bilaterally during MET throughout the intervention. The electrophysiological data of the contralateral side served as control. Neurological outcome was assessed by the modified Rankin Scale and National Institutes of Health Stroke Scale at 0, 7 and 90 days following intervention. Results: 20 patients were examined. MEPs and SSEPs were technically successful in 19 (95%) and 9 (45%) cases, respectively. Successful reperfusion was achieved in 16 cases. Functional recovery was observed in 14 patients. MEPs and SSEPs recovery status was a better predictor of functional recovery than successful reperfusion with a positive predictive value of 92%, 83% and 75% for MEPs, SSEPs and reperfusion, respectively. Conclusions: MEPs and SSEPs are safe and feasible methods of real-time monitoring of reperfusion success with respect to functional outcome during MET for acute ischaemic stroke.